THE Cat Behavior ANSWER BOOK : Solutions to Every Problem You'll Ever Face : Answers to Every Question You'll Ever Ask - Moore, Arden; Ambre, Matt; Peterson, Nancy (North Adams, MA : Storey Publishing, 2007)
Provides answers to more than 100 questions from cat owners. This book deciphers some of the most vexing feline foibles - scratching, howling, bed-hogging, leg rubbing, pillow peeing, and keyboard prancing - and provides practical advice on keeping your cat safe, healthy, and happy.
Keywords: Cats -- Behavior -- Miscellanea; Cats; Behavior, Animal